(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The use of various means of transport for plant protection measures in agriculture is not new. Its application increases productivity and reduces the cost of growing a variety of products. Conventional ground transport vehicles are self-propelled sprayers or those attached to agricultural tractors. The sprayed solution is stored in a container until it is applied or prepared on site. Inconveniences are created by the transfer of a large amount of detergent, its movement on uneven terrain, the processing of small and specific fields, the change of the working solution, etc. An alternative option is the use of unmanned vehicles – ground or in the air. They have their advantages and disadvantages. Their use is related to the implementation of a number of regulatory documents. However, they give autonomy to producers and enter more and more widely in agriculture. This article aims to compare the costs of using different means of transport as energy sources used for plant protection measures. As an example, when obtaining quantitative values, a sunflower crop typical for the country was used. In addition to standard costs, an attempt has been made to compare the carbon footprints of the use of different means of transport. The sensor part is made of standard soil moisture sensors, and the control part is entrusted to a single-board computer with the ability to control via a wireless network.